PERAN SEKOLAH DALAM PEMBINAAN KARAKTER TERHADAP SISWA BERPERILAKU MENYIMPANG DI SDN SEMANGAT DALAM 3 BATOLA - Netty Suharti (JURNAL SOCIUS, 2013)
The factors that cause the students have deviating behaviour in school. The research uses qualitative approach because it is in line with the statement of problem, the objective of study, and significances of the study. Therefore, the technique of data collection is based on interview, observation, and documentation. Finally, the research result in SDN Semangat Dalam 3 Batola says that any kinds of students’ deviating behavior illustrate the lowness of morality. It needs the serious attention from the stakeholder of school, parents, and society in order to form the personality in line with goals of national education. In a word, the research result ends that there have been students’ deviating behavior (1) because the role of parents are minus in guiding and controlling their children, (2) because the situation of home does not support the implimentation of education, (3) because the environment does not support the implimentation of education, (4) because of effect of media, such as TV, internet, and entertainment, and (5) because of no figure from the teachers. Because of such previous findings, it is important to make suggestions whether for the parents or the teachers. It means that program for making students get accustomed to the values of togetherness and nationalism in SDN Semangat Dalam 3 is very necessary. The teachers and parents surely are the models for the students to develop their competences in character building.   Key words: The role of school, the of constructing, character , the students’ deviating behavior